If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x-3-x=+7+2x
We move all terms to the left:
6x-3-x-(+7+2x)=0
We add all the numbers together, and all the variables
6x-x-(2x+7)-3=0
We add all the numbers together, and all the variables
5x-(2x+7)-3=0
We get rid of parentheses
5x-2x-7-3=0
We add all the numbers together, and all the variables
3x-10=0
We move all terms containing x to the left, all other terms to the right
3x=10
x=10/3
x=3+1/3
| X/20+x=28 | | 6=y−12−9/11y | | 17-2r=-7(5r+7) | | 1.56(h-2)+5=8.12 | | 58+3.75x=226.75 | | 2.4x=168 | | 7x-5+3x=7 | | x²-9x+36=0 | | -12x=-4/3 | | 32-3x=x+8 | | 29=−5a+4 | | G(x)=(1/2)x^2 | | Y=3x2-8÷4 | | 791.5+48.25x=1611.75 | | x-1+6x=34 | | 1+5x-4x=8 | | −4p+7=15 | | -21+2(8x-31)=88 | | 7x-3=6+9 | | (D^2+5D+6)y=0,y(0)=0,y(0)=15 | | 21=n(7) | | 6-2x+x=-2 | | 10(x+1)=3(x+3) | | 3(j-5)+-4=2 | | -9.1f-7.03=-5.4f | | 10(x+1)=3x+3 | | 36=3x+x+8 | | p(-3)=21 | | x+3-3=−6 | | (2x–5)(3x+8)=0 | | 7t+8=27 | | 15=-7x+5x+7 |